SCISSOR—Spinal Cord Injury Study on Small molecule-derived Rho inhibition: a clinical study protocol. Issue 7 (26th July 2016) - Kopp, Marcel A; Liebscher, Thomas; Watzlawick, Ralf; Martus, Peter; Laufer, Stefan; Blex, Christian; Schindler, Ralf; Jungehulsing, Gerhard J; Knüppel, Sven; Kreutzträger, Martin; Ekkernkamp, Axel; Dirnagl, Ulrich; et al.
Abstract : Introduction: The approved analgesic and anti-inflammatory drugs ibuprofen and indometacin block the small GTPase RhoA, a key enzyme that impedes axonal sprouting after axonal damage. Inhibition of the Rho pathway in a central nervous system-effective manner requires higher dosages compared with orthodox cyclooxygenase-blocking effects. Preclinical studies on spinal cord injury (SCI) imply improved motor recovery after ibuprofen/indometacin-mediated Rho inhibition. This has been reassessed by a meta-analysis of the underlying experimental evidence, which indicates an overall effect size of 20.2% regarding motor outcome achieved after ibuprofen/indometacin treatment compared with vehicle controls. In addition, ibuprofen/indometacin may also limit sickness behaviour, non-neurogenic systemic inflammatory response syndrome (SIRS), neuropathic pain and heterotopic ossifications after SCI. Consequently, 'small molecule'-mediated Rho inhibition after acute SCI warrants clinical investigation. Methods and analysis: Protocol of an investigator-initiated clinical open-label pilot trial on high-dose ibuprofen treatment after acute traumatic, motor-complete SCI. A sample of n=12 patients will be enrolled in two cohorts treated with 2400 mg/day ibuprofen for 4 or 12 weeks, respectively. The primary safety end point is an occurrence of serious adverse events, primarily gastroduodenal bleedings. Secondary end points are pharmacokinetics, feasibility and preliminary effects on neurological recovery, neuropathic pain and heterotopic ossifications. The primary safety analysis is based on the incidence of severe gastrointestinal bleedings. Additional analyses will be mainly descriptive and casuistic. Ethics and dissemination: The clinical trial protocol was approved by the responsible German state Ethics Board, and the Federal Institute for Drugs and Medical Devices. The study complies with the Declaration of Helsinki, the principles of Good Clinical Practice and all further applicable regulations. This safety and pharmacokinetics trial informs the planning of a subsequent randomised controlled trial. Regardless of the result of the primary and secondary outcome assessments, the clinical trial will be reported as a publication in a peer-reviewed journal. Trial registration number: NCT02096913; Pre-results.